INOVASI SOSIAL MELALUI PROGRAM CSR PT PLN (PERSERO) UNIT INDUK TANJUNG JATI B - Arifin, Miftah; Khoriul Anam, A.; Mahaputra, Wahyu (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
Empowerment is one of the strategies used in community development at this time. it can increase knowledge and power to reach a state of empowerment. one of the funding source empowerment programs comes from the Corporate Social Responsibility (CSR). PT. PLN (Persero) Tanjung Jati B Generation Main Unit sees that there are vulnerable groups that have the potential to be developed in their business management, these groups are the disabled community